Rapidly Display Glycan Symbols in 3D Structures: 3D-SNFG in LiteMol - Sehnal, David; Grant, Oliver C (Journal of proteome research, 2019)
The representation of carbohydrates in 3D space using symbols is a powerful visualization method, but such representations are lacking in currently available visualization software. The work presented here allows researchers to display carbohydrate 3D structures as 3D-SNFG symbols using LiteMol from a web browser (e.g., v.litemol.org/?loadFromCS=5T3X ). Any PDB ID can be substituted at the end of the URL. Alternatively, the user may enter a PDB ID or upload a structure. LiteMol is available at https://v.litemol.org and automatically depicts any carbohydrate residues as 3D-SNFG symbols. To embed LiteMol in a webpage, visit https://github.com/dsehnal/LiteMol .
Keywords: Carbohydrates; Polysaccharides; Software; Molecular Conformation; molekulární konformace; polysacharidy; sacharidy; software